Policy Advocacy for The Management of the Sunan Gunung Jati Religious Tourism Area: A Participatory Communication Study in Cirebon - Fiqih, Muhammad; Rachman, Arief; Faoziyah, Sitti (Strata International Journal of Social Issues, 2025)
This study investigates policy advocacy for the management of the Sunan Gunung Jati religious tourism area in Cirebon, focusing on the critical role of participatory communication and local actor engagement. Utilizing a descriptive qualitative approach through library research, the study analyzes scholarly literature and policy documents to understand how inclusive communication fosters community co-creation in policy planning, decision-making, and implementation. The findings reveal that participatory communication, rooted in Islamic community development principles, cultivates collective ownership and shared responsibility, essential for sustainable social transformation. The research highlights the indispensable function of diverse local actors—including religious leaders, youth groups, and NGOs—in mediating social dynamics such as conflicts of interest and resistance to change. Effective advocacy in this context demands context-sensitive communication strategies that balance cultural values, community aspirations, and policy objectives. This study concludes that strengthening community social capacity and clearly defining local actors' roles through holistic communication approaches are paramount for achieving efficient, equitable, and sustainable policy outcomes in culturally intricate environments. The insights offer valuable contributions for developing participatory policy advocacy theories and practices in Indonesia, particularly for religious tourism sites.